1997
DOI: 10.4049/jimmunol.159.5.2375
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 65 induced by gammadelta T cells prevents apoptosis of macrophages and contributes to host defense in mice infected with Toxoplasma gondii.

Abstract: We previously reported that gammadelta T cells mediate the expression of endogenous heat shock protein 65 (HSP65) in macrophages of mice with acquired resistance against infection with Toxoplasma gondii. We show here that HSP65 contributes to protective immunity by preventing apoptosis of infected macrophages. Macrophages of BALB/c mice, which readily acquired resistance to T. gondii infection with the low virulence Beverley strain, strongly expressed HSP65, and only a few of these macrophages underwent apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…HSP that have been involved in ␥␦ T cell activation (44) and contribute to resistance to apoptosis of macrophages infected by Toxoplasma gondii are over-expressed in infected APC (45). Of interest, HSP expression has also been implicated in resistance to NO-mediated cytolysis (46).…”
Section: Discussionmentioning
confidence: 99%
“…HSP that have been involved in ␥␦ T cell activation (44) and contribute to resistance to apoptosis of macrophages infected by Toxoplasma gondii are over-expressed in infected APC (45). Of interest, HSP expression has also been implicated in resistance to NO-mediated cytolysis (46).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, HSP65 appears to contributeto immune function by preventing apoptosis of infected macrophages and decreasing parasite survival and virulence. Under in vivo conditions, the Beverly strain, unlike the RH strain of T. gondii , induces the expression of HSP65 in the host gd-T cell [ 117 ].…”
Section: Regulated Cell Death (Rcd) and T Gondii I...mentioning
confidence: 99%
“…Others [ 51 , 65 , 67 ] have shown that the virulence of the strain-infecting phagocytes determines not only the production of cytokines, but also the level of HSP and the subsequent process of apoptosis. A high virulence of intracellular bacteria induces the apoptosis of infected monocytes/macrophages, while low virulence inhibits apoptosis and induces the development of an inflammatory process [ 51 , 66 , 67 , 68 ]. The high level of HSP produced by a cell infected with a low-pathogenic bacterium inhibits its apoptosis, probably as a result of accelerated maturation of Bcl-2 proteins [ 68 , 69 ].…”
Section: Peripheral Blood Mononuclear Cell (Pbmc) Apoptosis Induced B...mentioning
confidence: 99%
“…A high virulence of intracellular bacteria induces the apoptosis of infected monocytes/macrophages, while low virulence inhibits apoptosis and induces the development of an inflammatory process [ 51 , 66 , 67 , 68 ]. The high level of HSP produced by a cell infected with a low-pathogenic bacterium inhibits its apoptosis, probably as a result of accelerated maturation of Bcl-2 proteins [ 68 , 69 ]. Previously published data [ 51 , 64 , 66 , 68 , 69 , 70 , 71 , 72 ] suggest an anti-apoptotic effect of mycobacterial HSP70 and HSP65 on mononuclear phagocytes by protecting the integrity of the mitochondrion and/or by combining heat shock proteins with an apoptotic protease-activating factor or the N-terminal fragment of c-Jun, BAG-1 or Bcl-2.…”
Section: Peripheral Blood Mononuclear Cell (Pbmc) Apoptosis Induced B...mentioning
confidence: 99%
See 1 more Smart Citation